Study building a test to measure the level of offensive skill performance basketball players search on applicants and young - Abdul Karim, Helal (Journal of Physical Education, 2015)
Coaches and staff in the sports field seeks to develop and propose objective grounds fact to know the level reached by their athletes before, during and after the training to get to know a lot of questions they propose Aoausbandunha in their work. It is these questions ... Is that the training is going the right way? Does that followed the training led to a certain percentage of development and what is the ratio? Does this training appropriate or not appropriate to achieve the goals it ?, and many other questions Atsaelha this as long as he wants Coach access and identify the facts more ... Accordingly, these coaches work to propose several tests to measure the level at which the athletes have been adopted or uses a lot of trained experts or specialists science test and measurement associated with the type of efficiency in which they work and in this case, those standards and tests more accurate in measuring the effectiveness with which they work variables